FRIENDRAISING: BUILDING RELATIONSHIP IN FUNDRAISING (CASE STUDY PERKUMPULAN SUARA KITA) - Ika Trisnawati Susetyo; Ety Rahayu (UNIVERSITAS PAKUAN, 2022)
This study explains the importance of maintaining good relationships with donors in fundraising for Human service organizations. HSOs depend on fundraising for the survival of the organization and to support the running of their services. HSOs working on LGBT issues face difficulties in raising funds because of the discrimination they face. The case study of Perkumpulan Suara Kita with a qualitative approach illustrates the importance of maintaining good relationships with donors in supporting fundraising. Perkumpulan Suara Kita conducted public fundraising after facing obstacles in raising funds from donor organizations. Friendraising or relationship fundraising is one of the methods used by Perkumpulan Suara Kita in raising funds. Relationship fundraising allows Perkumpulan Suara Kita to raise funds and gain support for their work. The three public fundraising efforts carried out by Perkumpulan Suara Kita are very dependent on the loyalty of their donors; therefore, maintaining good relations with donors is one of the ways carried out by Perkumpulan Suara Kita. The Friendraising methods used by Perkumpulan Suara Kita are: be prompt, be interesting and memorable, be involving, be cheerful and helpful, be sincere and show commitment.